1978
DOI: 10.1021/bi00613a018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA polymerases α and δ from bone marrow

Abstract: DNA polymerases alpha and delta from rabbit bone marrow were purified to specific activities greater than 30 000 nM TMP incorporated (mg of protein)(-1)h(-1). alpha is quantitatively predominant. alpha and delta have the same reaction requirements and are both similarly sensitive to N-ethylmaleimide. The primary functional distinction is the association of 3' to 5' exonuclease activity with delta. Sedimentation coefficients obtained from zone sedimentation in glycerol gradients and Stokes radii values from gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…A representative purification of DNA polymerase alpha is outlined in Table 1. In comparison to our previously reported result (11) the yield of enzymatic activity has been increased by the inclusion of PMSF and PEG in the enzyme buffers. Previously, 7500 U of DNA polymerase were obtained from similar starting material after Step III; since these changes generally close to 40,000 U are obtained.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…A representative purification of DNA polymerase alpha is outlined in Table 1. In comparison to our previously reported result (11) the yield of enzymatic activity has been increased by the inclusion of PMSF and PEG in the enzyme buffers. Previously, 7500 U of DNA polymerase were obtained from similar starting material after Step III; since these changes generally close to 40,000 U are obtained.…”
Section: Resultscontrasting
confidence: 88%
“…The pH and conductivity of solutions were measured with a Radiometer pH meter and a Yellowspring conductivity bridge. Purification of DNA Polymerase Alpha DNA polymerase was purified from erythroid hyperplastic rabbit bone marrow through Step VIII but with several important modifications of previously described procedures (11,17). Briefly, rabbits were injected with phenylhydrazine to induce erythroid hyperplasia.…”
Section: Sds Slab Gel Electrophoresismentioning
confidence: 99%
“…Three forms of a-polymerase from HeLa cells are equally sensitive to aphidicolin, but one is significantly more sensitive to butylanilinouracil (59). A form of a-polymerase purifi ed from yeast (101, 102) and mammalian cells (103,104,462) has an associated 3'-5' exonuclease activity similar to that of HSV-l (105) and vaccinia virus (106) DNA polymerase. A mammalian enzyme from rabbit bone marrow, S-polymerase, may be the same as the D form of a-polymerase from calf thymus (95); both prefer poly d(A-T) as a primer template.…”
Section: A-polymerase Heterogeneitymentioning
confidence: 99%
“…Data on effects of the photoactivated DHE on DNA polymerase a and p in a permeabilized cell system indicated a strong inhibition in the activity of DNA polymerase a and a mild stimulation of the DNA polymerase p. Current concepts on the function of DNA polymerases in mammalian cells suggest that polymerases (Y and S are largely responsible for DNA replication in nuclei (Hammond et al, 1987;Weissback, 1979). DNA polymerase p has been implicated in DNA repair synthesis; however, recent studies also indicated an involvement of DNA polymerase a in DNA repair process (Berger er al., 1979;Byrnes and Black, 1985;Chung et a/., 1983;Thommes et al, 1986). In R3230 AC mammary tumor, Crute et al (1986) Fig.…”
Section: Discussionmentioning
confidence: 99%